2020
DOI: 10.3390/ijerph17062020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Community Water Fluoridation on Dental Caries Disparities in Adolescents

Abstract: Despite improvements in the prevalence of dental caries, disparities are still observed globally and in the U.S. This study examined whether community water fluoridation (CWF) reduced dental caries disparities in permanent teeth of 10-to 19-year-old schoolchildren in North Carolina. We used cross-sectional data representing K-12 schoolchildren in North Carolina (NC) public schools. A poisson regression model was used to determine whether the association between children's parental educational attainment and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…However, several such studies were captured in the systematic process and although they were not fully assessed by the reviewers, they seem to show dominant results, i.e. water fluoridation was found to save costs and to reduce caries [51,52]. Also fluoridated salt or milk-products may be cost-effective [53][54][55] and able to address inequities in dental health, but those studies in the present review were appraised as not transferable.…”
Section: Discussionmentioning
confidence: 99%
“…However, several such studies were captured in the systematic process and although they were not fully assessed by the reviewers, they seem to show dominant results, i.e. water fluoridation was found to save costs and to reduce caries [51,52]. Also fluoridated salt or milk-products may be cost-effective [53][54][55] and able to address inequities in dental health, but those studies in the present review were appraised as not transferable.…”
Section: Discussionmentioning
confidence: 99%
“…The age group of the included intervention studies was between 0 and 18 years old. With the exception of water fluoridation in three papers [22,26,27], the duration of the other studies varied from 19 months to 6 years. The follow-up time of four articles was 19 months to 2 years [16,17,19,25], and the other six articles had a longer duration time, between 4 and 6 years.…”
Section: Studies' Characteristicsmentioning
confidence: 99%
“…The included studies used different criteria in measuring the same outcome. Five studies assessed dental caries based on World Health Organization (WHO) criteria [19,22,24,26,27], three studies used International Caries Detection and Assessment System (ICDAS) criteria in assessing decayed teeth [17,20,25], and one article used the British Association for the Study of Community Dentistry (BASCD) to assess dental caries [28].…”
Section: Studies' Characteristicsmentioning
confidence: 99%
“…APC analysis revealed three trends in chewing difficulty: (1) there was an increase in chewing difficulty starting at around 60 years of age (age effect), (2) there was a steady decrease in chewing difficulty during the observation period (period effect), and (3) chewing ability improved with each successive generation born after 1951 (cohort effect). Regarding recent improvements in chewing ability, cohort effects were somewhat more important than period effects.Recent studies have suggested that oral health has been improving in many countries [1][2][3][4][5][6][7][8][9] , with decreased incidence of dental diseases and increased accessibility of dental care. Contributory factors could include improved proximal determinants of oral health (i.e., health behaviors and sugar consumption), as well as improving structural determinants (i.e., socioeconomic context and environmental context) over several decades.Oral health is affected by exposures throughout the entire life course, beginning in the prenatal period, and is strongly socially patterned 10 .…”
mentioning
confidence: 99%
“…Recent studies have suggested that oral health has been improving in many countries [1][2][3][4][5][6][7][8][9] , with decreased incidence of dental diseases and increased accessibility of dental care. Contributory factors could include improved proximal determinants of oral health (i.e., health behaviors and sugar consumption), as well as improving structural determinants (i.e., socioeconomic context and environmental context) over several decades.…”
mentioning
confidence: 99%